1992
DOI: 10.1159/000110921
|View full text |Cite
|
Sign up to set email alerts
|

Survival in Presenile Alzheimer's and Multi-lnfarct Dementias

Abstract: Duration of survival in patients who had died of presenile Alzheimer''s disease (AD) or presenile multi-infarct dementia (MID) in 13 mental hospitals in Scotland are described and contrasted. The duration of survival was significantly longer from symptom onset to death in AD (mean 7.4 years) than in MID (mean 5.8 years). Most of this difference was accounted for by a longer duration between symptom onset and presentation to hospital care in AD (mean 3.2 years) than in MID (mean 2.4 years). Age at onset and gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 6 publications
2
14
0
Order By: Relevance
“…If a survival analysis is used to measure duration of illness [ 15], a prevalence of 50.29 for broad Alzheimer's in the age band of 60-64 years can be calculated from the age-banded incidence rates [10], The authors have pointed out that the data for multi-infarct dementia and 'other dementias' recorded in their study should not be regarded as an accurate national estimate [12,15]. Given this proviso, the data of McGonigal et al suggest a preva lence rate of 116.35 per 100,000 per annum for 'all dementias' in the age band of 60-64 years (see Appendix for details).…”
Section: Conflicting Observations In Presenile Dementiamentioning
confidence: 99%
See 2 more Smart Citations
“…If a survival analysis is used to measure duration of illness [ 15], a prevalence of 50.29 for broad Alzheimer's in the age band of 60-64 years can be calculated from the age-banded incidence rates [10], The authors have pointed out that the data for multi-infarct dementia and 'other dementias' recorded in their study should not be regarded as an accurate national estimate [12,15]. Given this proviso, the data of McGonigal et al suggest a preva lence rate of 116.35 per 100,000 per annum for 'all dementias' in the age band of 60-64 years (see Appendix for details).…”
Section: Conflicting Observations In Presenile Dementiamentioning
confidence: 99%
“…The approximate prevalence of all dementias in the age bracket of 60-64 years was calculated from study data of McGonigal et al [10,15] and broad Alzheimer's incidence rates. An arbitrary mean illness time of 5 years in the case of multi-infarct dementia and 10 years for broad Alzheimer's disease and other dementias was assumed.…”
Section: Appendixmentioning
confidence: 99%
See 1 more Smart Citation
“…Two trained raters examined the hospital rec ords and included all early onset dementia patients in whom documented features of dementia were present before age 65. Patients were classified as 'probable' early onset AD, VaD or other dementia by standard criteria [4][5][6]. All VaD cases had Hachinski scores greater than 6 [7] and a history of at least one cerebro vascular accident.…”
Section: The Samplesmentioning
confidence: 99%
“…Many studies have reported that survival is reduced among patients with dementia, particularly in a setting of cerebrovascular disease. [1][2][3][4][5][6] It has also been reported that clinically stroke-free subjects with severe cognitive impairment are at an elevated risk of first stroke 7 and that stroke patients with dementia are at an elevated risk of long-term stroke recurrence compared with nondemented stroke patients. 8 The results of these studies suggest that the ability to accurately diagnose dementia could permit the identification of patients at risk of adverse events and the initiation of targeted interventions in those patients.…”
mentioning
confidence: 99%